In eiserner Zeit : Kriegswahrzeichen im Ersten Weltkrieg : ein Katalog - Schneider, Gerhard 1943- (bd edition, 2013)
Betrifft auch: Alexisbad, Annaburg, Aschersleben, Bernburg, Bitterfeld, Blankenburg (Harz), Burg b. Magdeburg, Dessau, Freyburg (Unstrut), Genthin, Güsten, Halberstadt, Haldensleben, Halle (Saale), Klötze, Magdeburg, Merseburg, Naumburg (Saale), Oebisfelde, Oschersleben, Osterfeld, Quedlinburg, Sangerhausen, Seehausen in der Altmark, Stendal, Stolberg (Harz), Thale, Wittenberg,